RELATIONSHIP OF THE LEPTIN GENE POLYMORPHISM ON THE PRODUCTION PERFORMANCE IN LOCAL AWASSI LAMBS - Abbas, E. R.; Mohamed, S. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted at the Animal Farm of the College of Agricultural Engineering Sciences, University of Baghdad during the period from 22/1/2022 to 2/4/2022. This study was conducted to investigate the effect of leptin gene polymorphism on the weight gain, digestibility and rumen fermentations of Awassi lambs. Forty Awassi lambs were selected at age 4-5 months, with an initial weight mean of 25.4 kg, and distributed randomly in individual pens. The results showed that there were three variations in SNP (G>A), GG, GA and AA it was 66.67, 30.56 and 2.7%, respectively, and the differences between them were highly significant (P≤0.01). No significant differences of leptin gene polymorphism were noticed on the percentage of volatile fatty acids (acetic, propionic and butyric) as well as on the percentage of ammonia nitrogen at all times (0,3 and 6 hours). There were highly significant differences (P≤0.01) in pH of the rumen fluid in GG variations at the times of 0 and 6 hours compared with GA it was 6.78 ± 0.03 and 6.76 ± 0.02, respectively. The results also showed that there were no significant differences in the leptin gene polymorphism on digestibility and weight gain. It can be concluded that the study of genetic variations of leptin gene had no effect on the performance of Awassi lambs.